2018
DOI: 10.1080/24725838.2018.1517702
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of Footwear Traction Performance across Flooring and Contaminant Conditions

Abstract: Background: To prevent slip and fall events at the workplace, mechanical slip testing is conducted on shoes. Such experiments may involve redundant testing across floorings and contaminant conditions, causing wasted time and effort. Purpose: Quantify the correlations between shoe traction across different contaminant-flooring conditions to reduce redundant slip testing efforts. Methods: The available coefficient-of-friction (ACOF) was quantified for 17 shoes across five floorings and three contaminant conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 31 publications
6
36
0
Order By: Relevance
“…It is worth noting that interaction effects including flooring were small and insignificant. Furthermore, other research has suggested that shoe traction performance across vinyl composite, quarry and ceramic floor surfaces are generalizable in the presence of canola oil (Chanda et al, 2018). Thus, these results are expected to be consistent when applied to other floorings.…”
Section: Discussionmentioning
confidence: 54%
“…It is worth noting that interaction effects including flooring were small and insignificant. Furthermore, other research has suggested that shoe traction performance across vinyl composite, quarry and ceramic floor surfaces are generalizable in the presence of canola oil (Chanda et al, 2018). Thus, these results are expected to be consistent when applied to other floorings.…”
Section: Discussionmentioning
confidence: 54%
“…The human slip biomechanics based on the parameters used to develop the slip tester were in-line with previous literature studies [17,22,32]. The maximum normal foot load of an average human [13], the slipping velocity observed in human slipping studies [17,33], and the ability to simulate different heel contact angles during slipping were incorporated into the device specifications. The outcomes of the device were validated using 10 formal shoes, tested across two different floorings in dry and wet conditions.…”
Section: Introductionmentioning
confidence: 70%
“…To reduce the overall slip risk, adequate shoe-floor traction is required [7][8][9][10][11]. Furthermore, external factors, such as fluid contaminated floorings, are known to increase the risk of slipping [10,12,13]. The resisting force required to ambulate across different flooring surfaces in barefoot conditions or when wearing shoes is typically quantified by the ratio of shear force to normal force, known as the available coefficient of friction (ACOF) [10,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a plethora of surrogate models exist for soft tissues such as the calcaneal heel pad [19,20], which have been characterized using indentation systems (measuring external load–deformation responses) [20], imaging (for internal strain measurements) [21], and experienced palpatory testing [22]. These surrogates have been used in anthropomorphic test devices for the study of injury risks associated with the lower extremity due to blast loading [14,19,23,24] and high impact loadings sustained in vehicular crashes [25,26]. Also, surrogate models have been employed in several studies to characterize the effect of personal protection equipment [27], and orthotic interventions for injury prevention [28,29].…”
Section: Introductionmentioning
confidence: 99%